(untitled) (The Peerian Journal, 2022)
To date, the pathogenetic process of coronary heart disease and hypertension should be based on complex reactions of neuroimmune interactions characterized by activation of proinflammatory cytokines, opiate receptors and endogenous opioid peptides. These changes are mediated by high activity at the the main regulatory systems that increase the resistance of the myocardium to acute and chronic ischemic damage. Nevertheless, there is insufficient data on the severity of these changes in the polymorbid course of coronary heart disease and hypertension, occurring against the background of anxiety and depressive disorders. In this connection, the purpose of this work was to study regulatory disorders at the level of the neuropeptide-cytokine pool of the immune system in patients with polymorbid cardiovascular pathology occurring against the background of anxiety and depressive disorders. A clinical examination of 85 patients (men) aged 35 to 45 years, with polymorbid cardiovascular pathology (ischemic heart disease in combination with hypertension of the second stage), occurring against the background of anxiety and depressive disorders, was conducted. To solve the tasks set out in this work, groups of comorbid patients with anxiety-depressive disorders were formed: 1st (n = 40) - patients with polymorbid pathology; 2nd (n = 20) – patients with ischemic heart disease; 3rd (n = 25) - patients with hypertension of the second stage; 4th (n = 30) – control (healthy persons). In order to study regulatory dysfunctions at the level of the neuropeptide-cytokine link of immunity, the state of the suprasegmental apparatus of the autonomic nervous system and the cytokine pool of the immune system were studied in the examination groups. Test systems were used to determine beta-endorphin, pro-inflammatory cytokines (TNFa, IL-1β, IL-6) and anti-inflammatory (IL-4, IL-10) spectrum in the blood serum of patients.